Social networks and fibromyalgia in the COVID-19 pandemic (Research, Society and Development, 2022)
Introduction: Fibromyalgia is a chronic non-communicable disease that causes widespread pain of the musculoskeletal system, in addition to psychosocial damage such as social isolation. With the pandemic of COVID-19, this public has become even more excluded and disadvantaged, with the use of social networks being of great importance. Objective: To analyze the scientific production about the influence of social networks on individuals with fibromyalgia during the coronavirus pandemic. Methodology: Integrative literature review, the PICO strategy was used, studies from MEDLINE, LILACS and IBECS were found. Results: 8 articles were selected. Discussion: The studies pointed out the difficulties that people affected by fibromyalgia face during the period of social isolation, but that the use of social networks as a communication tool promotes greater reception and is a differential for people affected with chronic illnesses such as fibromyalgia. Although social networks are a mechanism of great importance, without the filtering of content, they can contribute to the spread of fake news and conflicts of information. Conclusion: The current study observed how much social networks positively influenced the lives of people with fibromyalgia through Facebook groups, online forums, and telerehabilitation, with the main objective of directing and guiding these individuals who share the same feelings.